Development and Inter-Laboratory Validation of Diagnostics Panel for Detection of Biothreat Bacteria Based on MOL-PCR Assay - Jelinkova, Pavlina; Hrdy, Jakub; Markova, Jirina; Dresler, Jiri; Pajer, Petr; Pavlis, Oto; Branich, Pavel; Borilova, Gabriela; Reichelova, Marketa; Babak, Vladimir; Reslova, Nikol; Kralik, Petr (Microorganisms, 2020)
Early detection of biohazardous bacteria that can be misused as biological weapons is one of the most important measures to prevent the spread and outbreak of biological warfare. For this reason, many instrument platforms need to be introduced into operation in the field of biological warfare detection. Therefore the purpose of this study is to establish a new detection panel for biothreat bacteria (Bacillus anthracis, Yersinia pestis, Francisella tularensis, and Brucella spp.) and confirm it by collaborative validation by using a multiplex oligonucleotide ligation followed by polymerase chain reaction and hybridization to microspheres by MagPix detection platform (MOL-PCR). Appropriate specific sequences in bacterial DNA were selected and tested to assemble the detection panel, and MOLigo probes (short specific oligonucleotides) were designed to show no cross-reactivity when tested between bacteria and to decrease the background signal measurement on the MagPix platform. During testing, sensitivity was assessed for all target bacteria using serially diluted DNA and was determined to be at least 0.5 ng/µL. For use as a diagnostic kit and easier handling, the storage stability of ligation premixes (MOLigo probe mixes) was tested. This highly multiplex method can be used for rapid screening to prevent outbreaks arising from the use of bacterial strains for bioterrorism, because time of analysis take under 4 h.
Keywords: MOL-PCR; magnetic bead; detection panel; bioterrorism; biothreat bacteria